Low-carbon cement concrete as well as preparation method and application thereof

By adopting low-carbon cement concrete and its preparation method, the synergistic effect of nano-alumina and reduced fibers is used to solve the problems of high cost, large carbon emissions and poor stability of prefabricated components of ordinary cement concrete, and high strength, low carbon emissions and Prefabricated low-carb cement concrete components with good stability.

CN119462023APending Publication Date: 2025-02-18CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411851583.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing ordinary cement concrete prefabricated components have high cost, large carbon emissions, poor volume stability, and are prone to microcracks, affecting strength and durability.

Method used

Low-carb cement concrete is used, and its composition includes 10-15 wt%, coarse aggregate 40-45 wt%, fine aggregate 35-40 wt%, water 0.1-5.0 wt%, water reducer 0.1-2.0 wt%, nanometers 0.1 to 2.0 wt% alumina and 0.5 to 2.0 wt% reduce fibers, through the synergistic action of nano-alumina and reduce fibers, a network structure and filling effect are formed to optimize the microstructure of concrete.

Benefits of technology

It improves the volume stability and mechanical properties of low-carbon cement concrete, reduces cracks and deformation, and reduces carbon emissions, and is suitable for the preparation of prefabricated components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190723670000071
    Figure BDA0005190723670000071
  • Figure BDA0005190723670000081
    Figure BDA0005190723670000081
  • Figure BDA0005190723670000082
    Figure BDA0005190723670000082
Patent Text Reader

Abstract

The invention relates to low-carbon cement concrete as well as a preparation method and application thereof, and the low-carbon cement concrete is prepared from the following components in percentage by weight: 10 to 15 percent of low-carbon cement, 40 to 45 percent of coarse aggregate, 35 to 40 percent of fine aggregate, 0.1 to 5.0 percent of water, 0.1 to 2.0 percent of water reducing agent, 0.1 to 2.0 percent of nano aluminum oxide and 0.5 to 2.0 percent of shrinkage reducing fiber. The technical problem to be solved is how to provide the low-carbon cement concrete, so that the strength of the low-carbon cement concrete is improved, the requirement of a low-carbon cement concrete prefabricated part on the strength can be met, the volume stability of the low-carbon cement concrete prefabricated part is improved, cracking and deformation of the low-carbon cement concrete prefabricated part in the use process are favorably avoided, and the low-carbon cement concrete is not prone to cracking. And the durability of the low-carbon cement concrete prefabricated component is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of construction engineering, and in particular to a low-carbon cement concrete and a preparation method and application thereof. Background Art

[0002] With the rapid development of construction engineering technology, prefabricated components, as assembled buildings, have gradually become an important direction for the industry's transformation and upgrading due to their characteristics such as standardized design, factory production, assembly construction and integrated decoration.

[0003] As the core component of prefabricated buildings, precast concrete components have significant advantages in improving building quality, speeding up construction, reducing energy consumption and reducing environmental pollution. However, with the development of precast concrete component technology, market competition is becoming increasingly fierce. Precast components made of ordinary cement concrete have high costs, large carbon emissions, poor volume stability, and are prone to microcracks during construction or long-term use. The existence and expansion of these microcracks will inevitably affect the strength and durability of precast concrete components, which to a certain extent limits the widespread application of precast concrete components in the field of building materials.

[0004] Therefore, it is urgent to develop a new concrete and precast components thereof. Summary of the invention

[0005] The main purpose of the present invention is to provide a low-carbon cement concrete and a preparation method and application thereof. The technical problem to be solved is how to provide a low-carbon cement concrete that can improve the strength of the low-carbon cement concrete, meet the strength requirements of concrete precast components, and at the same time improve its volume stability, which helps to avoid cracking and deformation of the precast components during use.

[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. A low-carbon cement concrete proposed by the present invention comprises, by weight percentage, 10-15wt% of low-carbon cement, 40-45wt% of coarse aggregate, 35-40wt% of fine aggregate, 0.1-5.0wt% of water, 0.1-2.0wt% of water reducer, 0.1-2.0wt% of nano-alumina, and 0.5-2.0wt% of shrinkage-reducing fiber.

[0007] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0008] Preferably, in the aforementioned preparation method, the low carbon cement comprises: Portland cement clinker, desulfurized gypsum, composite materials, tempering components and grinding aids.

[0009] Preferably, in the aforementioned preparation method, the content of the Portland cement clinker is 15.0-48.0wt%.

[0010] Preferably, in the aforementioned preparation method, the content of the desulfurized gypsum is 5.0-7.0wt%.

[0011] Preferably, in the aforementioned preparation method, the content of the composite material is 46.8-70.0wt%.

[0012] Preferably, in the aforementioned preparation method, the content of the tempering component is 0 to 10 wt %.

[0013] Preferably, in the aforementioned preparation method, the content of the grinding aid is 0-0.1 wt%.

[0014] Preferably, in the aforementioned preparation method, the sum of the weight percentages of the above components in the low carbon cement is 100wt%.

[0015] Preferably, in the aforementioned preparation method, the composite material comprises at least two of fly ash, slag, volcanic ash admixture, sandstone and limestone.

[0016] Preferably, in the aforementioned preparation method, the coarse aggregate is crushed stone, and the coarse aggregate meets the continuous grading requirements.

[0017] Preferably, in the aforementioned preparation method, the fine aggregate is machine-made sand or river sand.

[0018] Preferably, in the aforementioned preparation method, the particle size of the coarse aggregate is 5 to 25 mm.

[0019] Preferably, in the aforementioned preparation method, the mass ratio of the coarse aggregate with a particle size of 5 to 10 mm to that of the coarse aggregate with a particle size of 10 to 25 mm is 1:1.

[0020] Preferably, in the aforementioned preparation method, the fineness modulus of the fine aggregate is 2.6.

[0021] Preferably, in the aforementioned preparation method, the mud content of the fine aggregate is less than 3.3%.

[0022] Preferably, in the aforementioned preparation method, the crushing index of the fine aggregate is less than 16%.

[0023] Preferably, in the aforementioned preparation method, the shrinkage-reducing fiber is selected from at least one of carbon fiber, glass fiber, organic fiber and basalt fiber.

[0024] Preferably, in the aforementioned preparation method, the residue on the 80 μm square hole sieve of the low carbon cement does not exceed 10%.

[0025] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing low-carbon cement concrete proposed by the present invention, it comprises the following steps:

[0026] S1. Mix and stir the formulated amount of low-carbon cement, water, water-reducing agent, nano-alumina, shrinkage-reducing fiber, fine aggregate and coarse aggregate to obtain a concrete mixture; the formulated amount, in terms of weight percentage, includes: 10-15wt% of low-carbon cement, 40-45wt% of coarse aggregate, 35-40wt% of fine aggregate, 0.1-5.0wt% of water, 0.1-2.0wt% of water-reducing agent, 0.1-2.0wt% of nano-alumina, and 0.5-2.0wt% of shrinkage-reducing fiber;

[0027] S2. Pour the concrete mixture into a mold and vibrate to obtain the low-carbon cement concrete.

[0028] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: A low-carbon cement concrete prefabricated component proposed in the present invention comprises the low-carbon cement concrete as described above.

[0029] By means of the above technical solution, the low-carbon cement concrete and its preparation method and application proposed by the present invention have at least the following advantages:

[0030] The low-carbon cement concrete provided by the present invention uses nano-alumina and shrinkage-reducing fibers as raw materials. The shrinkage-reducing fibers have good compatibility with low-carbon cement concrete, can form a mesh structure inside the concrete, link and reinforce the low-carbon cement concrete, and improve the volume stability of the low-carbon cement concrete. Nano-alumina can fill the internal pores of the low-carbon cement concrete, promote the generation of hydration products in the internal mesh structure, and improve the mechanical properties and self-cleaning ability of the low-carbon cement concrete. The filling effect and nucleation effect of nano-alumina combined with the physical barrier effect of the shrinkage-reducing fibers can promote the hydration reaction of cement, generate more hydration products, jointly optimize the microstructure of concrete, reduce pores and cracks, improve the density and strength of concrete, jointly control the shrinkage of concrete, improve the strength of concrete, reduce cracks and deformation caused by shrinkage, etc. In addition, the low-carbon cement concrete prefabricated components provided by the present invention have a low amount of cement clinker, and compared with ordinary silicate cement concrete prefabricated components, have excellent low-carbon emission properties.

[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0032] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a low-carbon cement concrete and its preparation method and its specific implementation method, structure, characteristics and effects proposed by the present invention in combination with the preferred embodiments.

[0033] The first aspect of the present invention provides a low-carbon cement concrete, which includes, by weight percentage: 10-15wt% low-carbon cement, 40-45wt% coarse aggregate, 35-40wt% fine aggregate, 0.1-5.0wt% water, 0.1-2.0wt% water reducer, 0.1-2.0wt% nano alumina, and 0.5-2.0wt% shrinkage reducing fiber.

[0034] The inventors found that adding nano-alumina to concrete can significantly improve the mechanical and deformation properties of concrete. Since the particle size of nano-alumina is extremely small, it can fill the tiny pores in concrete, reduce the porosity, and improve the density of concrete. Nano-alumina can participate in the hydration reaction of cement to generate more hydration products. These hydration products can further fill the pores and enhance the strength of concrete. At the same time, nano-alumina can also serve as the crystal nucleus of cement hydration products, promote the generation and crystallization of hydration products, and optimize the microstructure and durability of concrete. Shrinkage-reducing fibers are water-absorbent and can absorb excess water in concrete, reduce the shrinkage caused by water evaporation, and form a mesh structure in concrete, which can physically block the formation and expansion of cracks and improve the crack resistance of concrete. The filling effect and nucleation effect of nano-alumina combined with the physical barrier effect of shrinkage-reducing fibers can promote the hydration reaction of cement, generate more hydration products, jointly optimize the microstructure of concrete, reduce pores and cracks, improve the density and strength of concrete, jointly control the shrinkage of concrete, improve the strength of concrete, and reduce cracks and deformation caused by shrinkage.

[0035] The present invention specifically defines low carbon cement concrete, in which the components and contents thereof are, by weight percentage, 10-15wt% of low carbon cement, 40-45wt% of coarse aggregate, 35-40wt% of fine aggregate, 0.1-5.0wt% of water, 0.1-2.0wt% of water reducer, 0.1-2.0wt% of nano-alumina, and 0.5-2.0wt% of shrinkage-reducing fiber. The obtained concrete can achieve a 28d compressive strength of 55.5-68.5MPa, a 28d drying shrinkage of 374-472με, and a 28d splitting tensile strength of 5.6-8.2MPa, so that the concrete has excellent mechanical properties and volume stability.

[0036] According to the present invention, the low carbon cement comprises: 15.0-48.0wt% of silicate cement clinker, 5.0-7.0wt% of desulfurized gypsum, 46.8-70.0wt% of composite material, 0-10wt% of quenching and tempering component and 0-0.1wt% of grinding aid, and the sum of the weight percentages of the above components in the low carbon cement is 100wt%. The present invention controls the content of silicate cement clinker within the range of 15.0-48.0wt%, which can reduce the amount of silicate cement clinker, greatly reduce carbon emissions, and ensure the strength of low carbon cement concrete; the content of desulfurized gypsum is 5.0-7.0wt%, and the content of the effective component (calcium sulfate) is ≥75% to ensure the strength and quality stability of cement.

[0037] According to the present invention, the composite material is selected from at least two of fly ash, slag, volcanic ash admixture, sandstone and limestone. Fly ash and slag react chemically with calcium ions and other components in cement to form silicates and aluminates, and the metal ions (such as iron, calcium, magnesium) in fly ash and slag can promote the reduction and deoxidation process of hydroxide ions in silicates or aluminates, forming a large amount of Ca (OH) 2 and Mg (OH) 2 that can cover the surface of cement concrete, increase the durability of cement concrete, and thus improve the strength and stability of cement. In addition, volcanic ash admixtures will undergo secondary hydration in cement hardening slurry, consume Ca (OH) 2 crystals generated by cement hydration that are unfavorable to strength, and generate more CSH gel, further improving the coagulation and density of cement concrete. Volcanic ash admixtures can also effectively reduce the shrinkage of concrete and improve the concrete's resistance to chloride ion penetration, thereby improving the durability of the material.

[0038] According to the present invention, the tempering component can be selected by those skilled in the art according to actual needs, and the present invention does not specifically limit it. For example, the tempering component can be copper slag, steel slag or phosphorus slag.

[0039] According to the present invention, the grinding aid is conventionally selected in the art, and the present invention does not specifically limit it. For example, it can be triethanolamine, ethylene glycol or molasses.

[0040] In the present invention, the coarse aggregate is crushed stone, and the coarse aggregate meets the requirements of continuous grading, wherein the particle size of the coarse aggregate is 5 to 25 mm, and the mass ratio of the coarse aggregate with a particle size of 5 to 10 mm to the coarse aggregate with a particle size of 10 to 25 mm is 1:1, that is, in the coarse aggregate, the mass of the coarse aggregate of 5 to 10 mm and the coarse aggregate of 10 to 25 mm is equal, so as to form a better compact stacking state, aiming to improve the strength of concrete. Since the particle size and grading of the coarse aggregate have a significant effect on the performance of concrete. Therefore, the average particle size of the coarse aggregate of the present invention is within the above range, which is conducive to the subsequent preparation of precast concrete components that meet the quality requirements.

[0041] In the present invention, the fine aggregate is machine-made sand or river sand. The river sand has a better gradation, which is very beneficial to the workability of the low-carbon cement concrete of the present invention. The machine-made sand can adjust the fineness modulus and particle gradation of the machine-made sand according to the needs of the low-carbon cement concrete of the present invention, so as to be more suitable for practical use.

[0042] The fineness modulus of the fine aggregate is 2.6, which is a parameter to measure the coarseness of sand and gravel. Sand and gravel with a fineness modulus of 2.6 are medium sands, which are suitable for improving the strength of the concrete described in the present invention; the mud content of the fine aggregate is less than 3.3%, which refers to the percentage of the weight of the mud contained in the fine aggregate to the total weight. The mud content of the fine aggregate has a significant impact on the performance of the concrete. For example, when the mud content exceeds a certain limit, it may cause the slump of the concrete to decrease and the strength to decrease. The mud content of the fine aggregate described in the present invention is less than 3.3%, which helps to ensure the quality and performance of the concrete; the crushing index of the fine aggregate is less than 16%, which is an index to evaluate the crushing resistance of the fine aggregate, usually expressed as the ratio of the weight of the crushed aggregate to the total weight of the sample. The crushing index of the fine aggregate described in the present invention is less than 16%, which indicates that the fine aggregate used in the present invention has good crushing resistance and can ensure the overall stability of the concrete to a certain extent.

[0043] According to the present invention, the water reducer is a conventional choice in the art, and the present invention does not specifically limit it. For example, the water reducer can be one of a polycarboxylate water reducer, a naphthalene water reducer, an aminosulfonate water reducer, etc. The water reducer can effectively improve the fluidity of concrete, improve the workability of concrete, reduce the unit water consumption and unit cement consumption, save resources and improve the overall performance of concrete.

[0044] According to the present invention, the shrinkage-reducing fiber is selected from at least one of carbon fiber, glass fiber, organic fiber and basalt fiber. The shrinkage-reducing fiber is water-absorbent and can absorb excess water in the concrete, reduce the shrinkage caused by water evaporation, and form a mesh structure in the concrete, which can physically block the formation and expansion of cracks and improve the crack resistance of the concrete. In the present invention, the length of the shrinkage-reducing fiber is 3.0 to 4.9 mm. The shorter fiber can form an effective mesh structure in the concrete, which can disperse and absorb the stress inside the concrete, reduce the shrinkage of the concrete, and limit the expansion of microcracks, thereby effectively reducing the shrinkage cracks caused by drying of the concrete.

[0045] According to the present invention, the residue on the 80 μm square hole sieve of the low carbon cement does not exceed 10%, which is beneficial to mixing and improves the uniformity and stability of the low carbon cement concrete mixture.

[0046] A second aspect of the present invention provides a method for preparing low-carbon cement concrete, which comprises the following steps:

[0047] S1. Mix and stir the formulated amount of low-carbon cement, water, water-reducing agent, nano-alumina, shrinkage-reducing fiber, fine aggregate and coarse aggregate to obtain a concrete mixture; the formulated amount, in terms of weight percentage, is 10-15wt% of low-carbon cement, 40-45wt% of coarse aggregate, 35-40wt% of fine aggregate, 0.1-5.0wt% of water, 0.1-2.0wt% of water-reducing agent, 0.1-2.0wt% of nano-alumina, and 0.5-2.0wt% of shrinkage-reducing fiber;

[0048] S2. Pour the concrete mixture into a mold and vibrate to obtain the low-carbon cement concrete.

[0049] A third aspect of the present invention provides a low-carbon cement concrete prefabricated component, which includes the low-carbon cement concrete as described above.

[0050] According to the present invention, the low-carbon cement prefabricated components include prefabricated walls, prefabricated piles, prefabricated beams, prefabricated stairs, prefabricated bricks and the like.

[0051] According to the present invention, in the preparation process of the low-carbon cement prefabricated components, the steel bars used are selected from one of hot-rolled smooth round steel bars, cold-rolled ribbed steel bars, residual heat-treated steel bars and prestressed steel bars, and the diameter of the steel bars used is 6mm to 20mm.

[0052] In the present invention, the mold of the low-carbon cement prefabricated component is made according to actual needs, and those skilled in the art can select the mold material according to actual needs, such as metal, wood, ceramsite, steel bar or other materials.

[0053] In the present invention, during the preparation process of the low-carbon cement precast components, the precast components after concrete pouring need to be vibrated. Depending on the production process, the vibration mode is selected to be out-of-mold vibration or in-mold vibration to eliminate bubbles and excess concrete in the low-carbon cement precast components and ensure the density and flatness of the precast components.

[0054] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0055] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0056] Preparation Example

[0057] Preparation Example 1

[0058] 15wt% of Portland cement clinker, 7.0wt% of desulfurized gypsum, 70wt% of composite materials (fly ash and slag), 7.9wt% of tempering component (copper slag) and 0.1wt% of grinding aid (ethylene glycol) are mixed and ground until the residue on a 80μm square hole sieve does not exceed 10%, thereby obtaining low carbon cement.

[0059] Preparation Example 2-8

[0060] Preparation Examples 2-8 were carried out in the same manner as Preparation Example 1, except that the contents of the raw materials for preparing the low carbon cement were as shown in Table 1.

[0061] Table 1 Proportions of low carbon cement prepared in Preparation Examples 1-8

[0062]

[0063]

[0064] Example

[0065] In the following embodiments, the coarse aggregate used is crushed stone and meets the requirements of continuous grading, the particle size of the crushed stone is 5-25 mm, and the mass ratio of the crushed stone with a particle size of 5-10 mm to 10-25 mm is 1:1. The fineness modulus of the fine aggregate used is 2.6, the mud content is 3.0%, and the crushing index is 12%.

[0066] Example 1

[0067] As shown in Tables 2 and 3, 10 wt% of the low carbon cement obtained in Preparation Example 1, 2.4 wt% of water, 2 wt% of a water reducing agent, 0.1 wt% of nano alumina, 0.5 wt% of shrinkage reducing fiber (carbon fiber), 40 wt% of fine aggregate (mechanical sand) and 45 wt% of coarse aggregate (crushed stone) were mixed and stirred uniformly to obtain a concrete mixture, and the concrete mixture was poured into a mold and vibrated to obtain the low carbon cement concrete.

[0068] Embodiment 2-5

[0069] The low carbon cement used in Examples 2-5 corresponds to the low carbon cement obtained in Preparation Example 2-5. The contents of the raw materials used to prepare concrete in Example 2-5 are shown in Table 2, the types of the raw materials used to prepare concrete in Example 2-5 are shown in Table 3, and Example 2-5 is prepared according to the preparation method of Example 1.

[0070] Example 6

[0071] The low carbon cement used in Example 6 is a commercially available product. Example 6 was carried out according to the preparation method of Example 1. The contents and types of the raw materials used to prepare the low carbon cement concrete are shown in Table 2 and Table 3, respectively.

[0072] Comparative Examples 1-3

[0073] The low carbon cement used in Comparative Examples 1-3 corresponds to the low carbon cement obtained in Preparation Examples 6-8. Comparative Examples 1-3 are carried out in the same manner as in Example 1, the content of each raw material is shown in Table 2, and the type of each raw material is shown in Table 3.

[0074] Table 2 Concrete prepared by Examples 1-6 and Comparative Examples 1-3

[0075]

[0076]

[0077] Table 3 Types of concrete raw materials prepared in Examples 1-6 and Comparative Examples 1-3

[0078] Concrete Low Carbon Cement Coarse aggregate fine aggregate Shrinkage Reduction Fiber Example 1 Preparation Example 1 gravel Machine-made sand Carbon Fiber Example 2 Preparation Example 2 gravel river sand Fiberglass Example 3 Preparation Example 3 gravel Machine-made sand Carbon fiber, glass fiber, organic fiber Example 4 Preparation Example 4 gravel Machine-made sand Glass fiber, organic fiber Example 5 Preparation Example 5 gravel river sand Organic Fiber Example 6 Commercially available products gravel Machine-made sand Organic Fiber Comparative Example 1 Preparation Example 6 gravel Machine-made sand Carbon Fiber Comparative Example 2 Preparation Example 7 gravel Machine-made sand Carbon Fiber Comparative Example 3 Preparation Example 8 gravel Machine-made sand Carbon Fiber

[0079] Performance Testing

[0080] 1. Compressive strength test: Referring to GB / T50081 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the low-carbon cement concrete prepared in the embodiment and the cement concrete of the comparative example were tested for compressive strength. The results are shown in Table 4.

[0081] 2. Splitting tensile strength test. Referring to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the low-carbon cement concrete prepared in the embodiment and the cement concrete of the comparative example were subjected to splitting tensile strength tests. The recorded failure load was divided by the cross-sectional area of ​​the specimen to obtain the splitting tensile strength of the concrete in MPa. The results are shown in Table 4.

[0082] 3. Drying shrinkage test: refer to GB / T29417-2012 "Test method for drying shrinkage and cracking performance of cement mortar and concrete" to conduct drying shrinkage test on the low carbon cement concrete prepared in the embodiment and the cement concrete of the comparative example. Drying shrinkage in the present invention refers to microstrain (με), which is the ratio of the slight change in length of an object under the action of external force. 10000με is equivalent to 1% drying shrinkage. The results are shown in Table 4.

[0083] Table 4 Strength and drying shrinkage of concrete prepared in Examples 1-6 and Comparative Examples 1-3

[0084]

[0085]

[0086] From the above data, it can be seen that the low carbon cement concrete prepared in Examples 1-6 of the present invention has a 28d compressive strength of 55.5-68.5 MPa, a 28d drying shrinkage of 374-472 με, and a 28d splitting tensile strength of 5.6-8.2 MPa, indicating that the low carbon cement concrete of the present invention has excellent mechanical properties and volume stability.

[0087] It can be seen from Table 4 that in the present invention, no nano alumina is added to the concrete of Comparative Example 1, no shrinkage reducing fiber is added to the concrete of Comparative Example 2, and no nano alumina and shrinkage reducing fiber are added to the concrete of Comparative Example 3. The 28d compressive strength and 28d splitting tensile strength of the concrete prepared in Comparative Examples 1-3 are much lower than those in Examples 1-6, and the 28d drying shrinkage of the concrete prepared in Comparative Examples 1-3 is much greater than that in Examples 1-6.

[0088] Obviously, it can be seen from Table 4 that the present invention adds nano alumina and shrinkage-reducing fibers to concrete at the same time, and utilizes the synergistic effect of the two. The simultaneous use of the two significantly improves the compressive strength and splitting tensile strength of the concrete and reduces the drying shrinkage of the concrete.

[0089] The technical features in the claims and / or the specification of the present invention can be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the claims and / or technical features is also within the protection scope of the present invention.

[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A low carbon cement concrete, characterized in that: In terms of weight percentage, it includes: Low carbon cement 10-15wt%; Coarse aggregate 40~45wt%; Fine aggregate 35~40wt%; Water 0.1~5.0wt%; Water reducing agent 0.1~2.0wt%; Nano-alumina 0.1-2.0wt%; Shrinkage fiber 0.5~2.0wt%.

2. The concrete according to claim 1, characterized in that The low carbon cement comprises: silicate cement clinker, desulfurized gypsum, composite materials, tempering components and grinding aids; The content of the silicate cement clinker is 15.0-48.0wt%; The content of the desulfurized gypsum is 5.0-7.0wt%; The content of the composite material is 46.8-70.0wt%; The content of the tempering component is 0 to 10 wt %; The content of the grinding aid is 0-0.1wt%; The sum of the weight percentages of the above components is 100wt%.

3. The concrete according to claim 2, characterized in that The composite material includes at least two of fly ash, slag, volcanic ash mixed material, sandstone and limestone.

4. The concrete according to claim 1, characterized in that The coarse aggregate is crushed stone, and the coarse aggregate meets the requirements of continuous grading; The fine aggregate is machine-made sand or river sand.

5. The concrete according to claim 4, characterized in that The particle size of the coarse aggregate is 5-25 mm, wherein the mass ratio of the coarse aggregate with a particle size of 5-10 mm to that of 10-25 mm is 1:

1.

6. The concrete according to claim 4, characterized in that The fineness modulus of the fine aggregate is 2.6; the mud content of the fine aggregate is less than 3.3%; and the crushing index of the fine aggregate is less than 16%.

7. The concrete according to claim 1, characterized in that The shrinkage-reducing fiber is selected from at least one of carbon fiber, glass fiber, organic fiber and basalt fiber.

8. The concrete according to claim 1, characterized in that The residue on the 80μm square hole sieve of the low carbon cement does not exceed 10%.

9. A method for preparing low-carbon cement concrete, characterized in that: It includes the following steps: S1. Mix and stir the formulated amount of low-carbon cement, water, water-reducing agent, nano-alumina, shrinkage-reducing fiber, fine aggregate and coarse aggregate to obtain a concrete mixture; the formulated amount, in terms of weight percentage, includes: 10-15wt% of low-carbon cement, 40-45wt% of coarse aggregate, 35-40wt% of fine aggregate, 0.1-5.0wt% of water, 0.1-2.0wt% of water-reducing agent, 0.1-2.0wt% of nano-alumina, and 0.5-2.0wt% of shrinkage-reducing fiber; S2. Pour the concrete mixture into a mold and vibrate to obtain the low-carbon cement concrete.

10. A low-carbon cement concrete prefabricated component, characterized in that: It comprises the low-carbon cement concrete according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Concrete reinforcing agent with strong impermeability and flexural resistance and concrete

    CN110218016A

  • Nano silicon dioxide and basalt fiber synergistically enhanced recycled concrete and preparation method thereof

    CN114656206A

  • Nanometer material composite ultra-high performance concrete

    CN114890742A

  • Multi-element low-carbon less-clinker composite cement and preparation method thereof

    CN114920473A

  • High-performance low-carbon concrete and preparation method thereof

    CN117164312A